Epistemologi Filsafat Islam - Alkhadafi, Rahmad (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2024)
Islam pays great attention to epistemology by trying to combine knowledge that comes from revelation with knowledge obtained through human reason. Divine knowledge, given through revelation in the Koran and Hadith, is harmonized with knowledge obtained through human reason. Muslim philosophers and scholars have attempted to unite these two sources of knowledge to create a complete understanding. This research uses a qualitative approach using library research. The aim of this article is to explore and analyze aspects of epistemology in Islamic philosophy and their implications for the development of philosophical thought in the Islamic world. The results of this research show that bayani focuses on textual understanding, irfani on intuitive and mystical knowledge, while burhani emphasizes a rational and logical approach. These three aspects together create a comprehensive epistemological framework in the Islamic intellectual tradition, offering a holistic and integrative view of knowledge